1999
DOI: 10.1116/1.581700
|View full text |Cite
|
Sign up to set email alerts
|

Ultralarge scale integrated metallization and interconnects

Abstract: The use of copper interconnects enables higher speed, enhanced electromigration lifetime reliability, reduced power consumption, and ultimately reduced manufacturing cost for silicon integrated circuits. The formation of planarized inlaid copper interconnects requires sequential deposition of a continuous diffusion barrier layer followed by copper seed/fill deposition and chemical-mechanical polishing (CMP). In this article we present a vacuum-integrated cluster tool technology for deposition of a TaN barrier … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
0

Year Published

2001
2001
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(24 citation statements)
references
References 0 publications
0
24
0
Order By: Relevance
“…Conformal coverage in metal and dielectric thin-film processing is a key factor for ultra-large scale integration (ULSI) applications or diffusion barrier layers; [1,2] however, as the device feature sizes constantly reduce, achieving conformality at these length scales becomes more challenging. Similar conformality challenges also apply to polymer thin-film coatings used for organic light emitting devices (OLEDs), medical implants, or membrane applications where conformality is a crucial requirement.…”
Section: Introductionmentioning
confidence: 99%
“…Conformal coverage in metal and dielectric thin-film processing is a key factor for ultra-large scale integration (ULSI) applications or diffusion barrier layers; [1,2] however, as the device feature sizes constantly reduce, achieving conformality at these length scales becomes more challenging. Similar conformality challenges also apply to polymer thin-film coatings used for organic light emitting devices (OLEDs), medical implants, or membrane applications where conformality is a crucial requirement.…”
Section: Introductionmentioning
confidence: 99%
“…For example, patterned alkanethiols acted as a positive template (i.e., Cu was deposited only in the irradiated areas [413,414]), whereas SAMs of o-(40-methylbiphenyl-4-yl)-dodecyl thiol and of 1-10-biphenyl-4-thiol acted as negative templates where Cu was deposited only on the non-irradiated areas [415]. The electrodeposition of copper has attracted enormous interest for microelectronics as a reliable tool to deposit high-conductive material for on-chip interconnections [416]. Völker et al [417] studied the fabrication of copper nanostructures, and demonstrated a material preparation procedure combining e-beam lithography on self-assembled monolayers with selective electrochemical deposition.…”
Section: Metalsmentioning
confidence: 99%
“…However, copper is known to diffuse rapidly through SiO 2 . [1][2][3][4][5][6] Thus, it is necessary to introduce a diffusion barrier between the Cu and the dielectrics. In addition, Cu also suffers from poor adhesion to SiO 2 dielectrics, due to its inability to reduce SiO 2 , which causes a rapid mass diffusion along the interface and surfaces, resulting in degraded reliability.…”
Section: Introductionmentioning
confidence: 99%